Determinats of The Parenting Experiences for Toodlers and Pre-School Children - Simatupang, Erna Juliana; Novfrida, Yizri; Mafluha, Yanasita; Nugraha, Rd. Deden Gumilar (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Stunted growth in child development will pose a risk of various diseases, it is still found 11.5% of children under five in Indonesia have developmental disorders. This study aims to determine the determinants of childcare experience factors for toddlers and pre-school age. Using secondary data from the results of the 2019 BKKBN Program Performance and Accountability Survey (SKAP). This type of research is cross sectional. The study population was families who have toddlers and pre-school children, the study sample was 1316, with exclusion and inclusion criteria. Data analysis used univariate, bivariate and multivariate analysis, using the chi square test and logistic linear regression. From the research results, it was found that the related factors are; education level (p value = 0.00), number of children under five (P = 0.00), welfare level (P= 0.00), area of residence (P = 0.00). The most related factors were the level of education (OR 1.610) and the number of children (OR 2.421). It is hoped that the government can organize training programs or parenting classes and use local resources to improve childcare skills in families.